Radio resource scheduling in LTE-advanced system with carrier aggregation - Al-Shibly, Mohammed Abuljawad M.; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (Asian Research Publishing Network (ARPN), 2015)
This study attaches the downlink radio resource allocation problem in the LTE-Advanced system by introducing an enhanced cross component carrier proportional fair algorithm. The importance of the study comes from the fact that almost all prior studies were not able to create a balance between the throughput and fairness of the system to optimize its efficiency. Therefore, this study attempts to overcome this difficulty by proposing an enhanced cross component carrier proportional fair algorithm in order to maximize the system throughput while at the same time maintaining fairness of radio resource allocation among all UEs. The simulation results show that the proposed algorithm exceeds the previous studies, which involves that the enhancement of the algorithm manages to guarantee a balance between increasing the average system throughput and maintaining good fairness among all UEs.